2005
DOI: 10.1038/sj.eye.6702136
|View full text |Cite
|
Sign up to set email alerts
|

Corneal topographic response to intraocular pressure reduction in patients with vernal keratoconjunctivitis and steroid-induced glaucoma

Abstract: Purpose: To study the corneal topographic response to IOP reduction in vernal keratoconjunctivitis (VKC) with steroidinduced glaucoma. Methods: A total of 42 eyes of 21 patients with VKC and steroid-induced glaucoma (Group I) and 66 eyes of 33 patients with VKC without glaucoma (Group II) underwent an evaluation by Orbscan topography. In eyes with glaucoma, the IOP was controlled medically and the corneal topography was repeated at 3 months to evaluate effect on corneal parameters. Results: The mean baseline I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Steroids can be highly effective, but there are risks of glaucoma, superinfection with viruses and bacteria due to local immunosuppression, delayed wound healing, and cataract induction warrant cautious use of topical steroids [17][18][19][20][21][22][23][24]. Therefore, non-steroidal medications are desirable for the treatment of VKC as alternative, but new topical agents with dual antiallergic activity (mast cell stabilizers and antihistamine) may also be used for long-term treatment of allergic inflammation to alleviate signs and symptoms of the disease [21,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Steroids can be highly effective, but there are risks of glaucoma, superinfection with viruses and bacteria due to local immunosuppression, delayed wound healing, and cataract induction warrant cautious use of topical steroids [17][18][19][20][21][22][23][24]. Therefore, non-steroidal medications are desirable for the treatment of VKC as alternative, but new topical agents with dual antiallergic activity (mast cell stabilizers and antihistamine) may also be used for long-term treatment of allergic inflammation to alleviate signs and symptoms of the disease [21,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…These differences in corneal topography between glaucomatous and CCT-matched healthy subjects and the significant correlation between the IOP level and the posterior corneal elevation we found in the POAG group suggest that they are somehow related to the glaucomatous disease. 25 Reports of transient keratectasia with evident posterior corneal surface elevation after episodes of acute IOP elevation have suggested that high IOP could compress fluid out of the corneal stroma, 12 causing an inverse relationship between the IOP and corneal thickness. We do not know exactly the reason for the increased elevation of the posterior corneal surface in our patients with POAG.…”
Section: Discussionmentioning
confidence: 99%
“…6 The importance of the CCT in patients with glaucoma seems to depend not only on its effect as a source of error in IOP measurement 7 but also because it seems to be a significant risk factor, independent of IOP, for the development of glaucomatous damage in patients with OHT and for POAG in the general population. 11 Using the Orbscan II, Dada et al 12 found a significant decrease in the posterior corneal elevation after lowering the IOP in eyes with steroid-induced glaucoma; but to the best of our knowledge, no previous study has analyzed the anterior and posterior corneal curvatures of POAG patients using this device. 9 Ultrasound-based devices are the most widely used for measuring the corneal thickness 10 ; however, this technology offers limited information about the overall corneal morphology.…”
mentioning
confidence: 99%
“…Topical steroids have been shown to be effective in controlling ocular surface inflammation in VKC, but they should be used with particular caution due to their ocular side effects including glaucoma and cataract formation [2,4,[9][10][11][12][13]. As alternative, new topical agents with dual antiallergic activity (mast cell stabilizers and antihistamine) may be used for long-term treatment of allergic inflammation, to alleviate signs and symptoms of the disease [4,12,[14][15][16][17][18][19][20].…”
Section: Treatmentsmentioning
confidence: 99%